Formation of poly(o-anisidine) coatings on copper from aqueous salicylate solution - Chaudhari, Sudeshna; Mandale, A. B.; Patil, K. R.; Sainkar, S. R.; Patil, P. P. (Surface & Coatings Technology, 2006)
Poly(o-anisidine) coatings have been electrosynthesized by using cyclic voltammetry on copper from an aqueous salicylate medium. Cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy and X-ray photoelectron spectroscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-anisidine on copper substrate. Cyclic voltammetry accompanied by the X-ray photoelectron spectroscopy was used to characterize the surface modifications induced by polarizing the copper substrate in the aqueous salicylate solution (without monomer). It was shown that the polarization of the copper in the aqueous salicylate medium results into the passivation of its surface via the formation of Cu(2)O and/or copper salicylate complex. It was found that the electrochemical polymerization of o-anisidine takes place after the passivation of the copper substrate via fort-nation of Cu(2)O and/or copper salicylate complex and results into the formation of shiny, uniform and strongly adherent poly(o-anisidine). The optical absorption spectroscopy reveals the formation of emraldine salt form of poly(o-anisidine). This study offers an electrochemical polymerization recipe to synthesize strongly adherent poly(o-anisidine) coating on copper from aqueous media for possible use in corrosion protection application. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; corrosion protective coatings; cyclic voltammetry; poly(o-anisidine) coatings

Anticorrosive properties of electrosynthesized poly(o-anisidine) coatings on copper from aqueous salicylate medium - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Journal of Physics D-Applied Physics, 2007)
Poly( o-anisidine) ( POA) coatings were electrosynthesized on copper ( Cu) from an aqueous solution containing o-anisidine and sodium salicylate by using cyclic voltammetry, galvanostatic and potentiostatic modes. The extent of corrosion protection offered by these coatings to Cu in aqueous 3% NaCl solution was evaluated by the open circuit potential measurements, potentiodynamic polarization technique and electrochemical impedance spectroscopy. Potentiodynamic polarization and electrochemical impedance spectroscopy studies reveal that the POA acts as a protective layer on Cu against corrosion in 3% NaCl solution. The positive shift in the corrosion potential for the POA-coated Cu indicates the protection of the Cu surface by the POA. The POA coating synthesized by using cyclic voltammtery, galvanostatic and potentiostatic modes reduces the corrosion rate of Cu almost by a factor of 100, 100 and 7, respectively. The cyclic voltammetry was proved to be the better mode to adopt for the synthesis of more compact and strongly adherent POA coatings on Cu. The coatings synthesized by this mode were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. It was found that the electrochemical polymerization of o-anisidine on Cu takes place after the passivation of its surface via the formation of Cu2O and/or copper salicylate complex and results in the generation of shiny, uniform and strongly adherent POA coatings. The optical absorption spectroscopy reveals the formation of the emeraldine salt form of POA. The results of this study clearly ascertain that the POA has outstanding potential to protect Cu against corrosion in a chloride environment.

Poly(o-ethylaniline) coatings for stainless steel protection - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Progress In Organic Coatings, 2007)
The poly(o-ethylaniline) coatings were electrochemically synthesized on 304-stainless steel by using cyclic voltammetry from an aqueous salicylate medium. Cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethyaniline on 304-stainless steel. The performance of poly(o-ethylaniline) as protective coating against corrosion of 304-stainless steel in aqueous 3% NaCl was evaluated by the open circuit potential measurements, potentiodynamic polarization technique, cyclic potentiodynamic polarization measurements and electrochemical impedance spectroscopy. The results of the potentiodynamic polarization and cyclic potentiodynamic polarization demonstrate that the poly(o-ethylaniline) coating provides excellent protection to both localized and general corrosion of 304-stainless steel. The corrosion potential was about 0.190 V more positive in aqueous 3% NaCl for the poly(o-ethylaniline) coated steel than that of bare steel and reduces the corrosion rate of steel almost by a factor of 20. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings; stainless steel

Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis

Poly(o-anisidine) coatings on brass: synthesis, characterization and corrosion protection - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Current Applied Physics, 2009)
Poly(o-anisidine) (POA) coatings were synthesized on brass by electrochemical polymerization of o-anisidine in aqueous salicylate solution by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy., Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The corrosion protection aspects of POA coatings on brass in aqueous 3% NaCl solution were investigated by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The potentiodynamic polarization measurements show that the POA coating has ability to protect the brass against corrosion. The corrosion potential was about 0.204 V versus SCE more positive for the POA coated brass than that of uncoated brass and reduces the corrosion rate of brass almost by a factor of 800. The corrosion behavior of the POA coatings was also investigated by EIS through immersion tests performed In aqueous 3% NaCl solution. The evolution of the impedance parameters with the immersion time was studied and the results Show that the POA acts as a protective coating on brass against corrosion in 3% NaCl solution. The water uptake and delamination area were also determined to further support the corrosion protection performance of the POA coating. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: brass; conducting polymers; Corrosion resistant coatings; cyclic voltammetry; Electrochemical impedance spectroscopy; Electrochemical polymerization; poly(o-anisidine)

Synthesis and corrosion protection aspects of poly(o-toluidine)/CdO nanoparticle composite coatings on mild steel - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Journal of Coatings Technology and Research, 2010)
This study examines the possibility of using poly(o-toluidine)/CdO (POT-CdO) nanoparticle composite coating for corrosion protection of mild steel in chloride environment. The POT-CdO nanoparticle composite coating was synthesized on mild steel from aqueous tartrate solution containing CdO-nanoparticles (size similar to 18 nm) by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction measurements. The corrosion protection aspects of the resulting POT-CdO nanocomposite structure were investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of these investigations reveal that the POT-CdO nanoparticle composite acts as a protective coating on mild steel and reduces the corrosion rate of mild steel almost by factor of 70.
Keywords: CdO; Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Mild steel; Nanocomposites; Poly(o-toluidine)